2021
DOI: 10.1177/1759720x211058502
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and risk of invasive fungal infections in systemic lupus erythematosus: a nationwide population-based cohort study

Abstract: Introduction: Infections are a leading cause of mortality in patients with systemic lupus erythematosus (SLE). Among various infections, invasive fungal infections (IFIs) have a particularly high mortality rate; however, studies examining IFIs in patients with SLE are limited. Methods: Patients diagnosed as having SLE between 1997 and 2012 were enrolled from Taiwan’s National Health Insurance Research Database along with age- and sex-matched non-SLE controls at a ratio of 1:10. IFIs were identified based on In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
(49 reference statements)
2
6
0
Order By: Relevance
“…This study also agrees with previous studies that suggest the use of high-dose corticosteroids is a predisposing factor to candidiasis [ 8 , 15 , 16 ]. There are several mechanisms proposed for how corticosteroid use can lead to candidiasis.…”
Section: Discussionsupporting
confidence: 93%
“…This study also agrees with previous studies that suggest the use of high-dose corticosteroids is a predisposing factor to candidiasis [ 8 , 15 , 16 ]. There are several mechanisms proposed for how corticosteroid use can lead to candidiasis.…”
Section: Discussionsupporting
confidence: 93%
“…Cumulative exposure of systemic glucocorticoids or recent high-dose glucocorticoid treatment has the risk of invasive fungal infections and is associated with an increased risk of mortality in SLE. 8,25,26 Furthermore, the present study revealed that the average daily dose of systemic glucocorticoids equivalent to >10 mg of prednisolone increases the mortality in adult SLE patients who ever received hospital admission. A higher average daily dose of steroid treatment is aimed to control disease activities in severe SLE patients, and the risk of sepsis usually increased according to our risk factor analysis.…”
Section: Discussionsupporting
confidence: 49%
“…Fungal infections are eleven times more frequent in lupus patients than healthy controls with an overall IR for fungal infections in Taiwan between 1997 and 2012 of 2.1/1000 person years 26 and Candidiasis the most frequent (>50%) fungal infection and IR for Cryptococcus three times higher than for Aspergillus. As Candida infection has been shown to have low validity (PPV 20%) in administrative data in contrast to Cryptococcus (PPV 100%) and Aspergillus (67%), 27 we excluded candida infections but found a similarly IR difference for Cryptococcus and Aspergillus (IR 2.72 vs 0.57 respectively).…”
Section: Discussionmentioning
confidence: 97%